OPTIMALISASI PERAN DEWAN PENGAWAS SYARIAH (DPS) DALAM PERBANKAN SYARIAH DI MEDAN - Rokan, Mustapa Khamal (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2017)
Structure of sharia supervision board implements Islamic Economics law into business transactions through sharia supervision processes. This article aims to define sharia supervision and examine sharia supervisory councils. It also discusses the importance of the hierarchical position DPS and evaluates their objectives and functions. It reviews a wide range of theoretical literatures, especially recent proceedings of relevant conferences in Indonesia along with the standards of National Sharia board or Dewan Syariah Nasional, Dewan Ulama Indonesia (DSN-MUI). A framework for understanding the role of the DPS developed suggests a set of objectives and functions for the DPS. The paper finds a lack of standardization among the DPS concerning the position of the DPS within the corporate hierarchy. DPS cannot be able to give innovation product to solve sharia banks problems. Therefore, sharia supervision board needs to be valued seriously and well.